If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 9) = 9x + -45 Reorder the terms: 2(9 + x) = 9x + -45 (9 * 2 + x * 2) = 9x + -45 (18 + 2x) = 9x + -45 Reorder the terms: 18 + 2x = -45 + 9x Solving 18 + 2x = -45 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 18 + 2x + -9x = -45 + 9x + -9x Combine like terms: 2x + -9x = -7x 18 + -7x = -45 + 9x + -9x Combine like terms: 9x + -9x = 0 18 + -7x = -45 + 0 18 + -7x = -45 Add '-18' to each side of the equation. 18 + -18 + -7x = -45 + -18 Combine like terms: 18 + -18 = 0 0 + -7x = -45 + -18 -7x = -45 + -18 Combine like terms: -45 + -18 = -63 -7x = -63 Divide each side by '-7'. x = 9 Simplifying x = 9
| 105+99+3x=180 | | -X^2=-289 | | 729=81x | | 19x+8=19x-8 | | 400/2x=244 | | 2458=2*3.14*17.64+2*3.14*4.2*h | | 2x+(x+1)+10=3x+12 | | 8.47=12.4cos(6.31t) | | 12x-3=22+2x | | 4+2w=-6 | | Y=-4x^3+100x | | -6x+3(-4x-24)=-180 | | 2x-7+4x+14=49 | | D^2-10d+21=0 | | 6y-24=24x | | 3d+7=9 | | 35=5x+y | | 15-xy+5y-3x=0 | | w-7.14=5.74 | | k^2-6-16=0 | | 9ab-12a^2+6ab^2=0 | | 624.546=2*3.14*26.01+2*3.14*5.1*h | | 8=32b | | -1(p+5)=-3(2p-10) | | 625=25x | | 0.5(4x+7)=0.6-(x-3) | | 4.3x+25.8=64.5-8.6x | | 21a=7 | | 1/3x+2+1/2x-3=90 | | V=567 | | 3(x-4)-12+2x-9= | | 4.84x=2x |